UPAYA GURU DALAM MENGEMBANGKAN KOMPETENSI DASAR ANAK USIA DINI PADA RAUDHATUL ATHFAL (RA) DI KOTA BENGKULU - Yeti Herliza (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2016)
The results of this thesis study describes the first, the efforts of teachers in developing basic competence on themoral values of children usiadini among others: 1) to instill the value of politeness and respect for elders or teachers. 2)familiarize the values of discipline and responsibility to the task given. 3) to instill the values of honesty and openness tothe environment 4) familiarize the values of sacrifice and sincerity in giving and helping a friend 5) inculcate the habitof life-saving 6) to instill the values of patience in completing a job 7) inculcate love in friends , Both efforts of teachersto develop basic competence in religious values early childhood among others: 1) to instill confidence in the six pillarsof faith and keataatannya 2) to instill confidence in the 5 pillars of Islam and its practice 3) used to always melafazkankalimah tayyibah in life 4) to instill confidence in the magnitude of the love of God Almighty 5) recognize and instillbeauty beautiful Names 5) recognize and instill the values contained in the two Islamic holidays